2020
DOI: 10.1038/s41598-020-57531-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics of pellicle and saliva in children with different caries activity

Abstract: pellicle is the initial proteinaceous layer that is formed almost instantaneously on all solid surfaces in the oral cavity. it is of essential relevance for any interactions and metabolism on the tooth surface. Up to now, there is no information on the metabolome of this structure. Accordingly, the present study aims to characterise the metabolomic profile of in-situ pellicle in children with different caries activity for the first time in comparison to saliva. Small molecules such as carbohydrates, amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…There is unavoidable and unobserved complexity in what is sampled and measured in observational supragingival biofilm metabolomics studies like the present one. For example, the origins of the metabolome: Schulz et al (2020) recently conducted targeted metabolomics analyses of initially formed (10 min) pellicle in young children and found that the identified metabolites were not significantly different from what was quantified in saliva. Importantly, the most abundant metabolites, including acetic acid, propionic acid, glycine, serine, galactose and mannose, lactose, glucose, palmitic acid, and stearic acid, were identified in the virtual absence of bacterial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…There is unavoidable and unobserved complexity in what is sampled and measured in observational supragingival biofilm metabolomics studies like the present one. For example, the origins of the metabolome: Schulz et al (2020) recently conducted targeted metabolomics analyses of initially formed (10 min) pellicle in young children and found that the identified metabolites were not significantly different from what was quantified in saliva. Importantly, the most abundant metabolites, including acetic acid, propionic acid, glycine, serine, galactose and mannose, lactose, glucose, palmitic acid, and stearic acid, were identified in the virtual absence of bacterial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to early phases of biofilm formation and by the interconnection with other species to the establishment of mature plaque (see next chapter). However, it is important to note that according to recent studies, the ultrastructure, enzyme activities, and proteomic profile of the acquired pellicle do not show major differences between otherwise healthy caries-active and inactive subjects [ 67 , 72 , 73 ].
Fig.
…”
Section: Bioadhesion In the Oral Cavitymentioning
confidence: 99%
“…Furthermore, it is necessary to normalize the data obtained in each group to avoid errors associated with the raw data [126,128]. Traditionally, many researchers use the p-value as the main statistical tool in order to identify analytes whose variation is statistically significant [129][130][131][132]. However, this approach is extremely limited and often results in numerous false positives and negatives [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) is the most common method used in unsupervised analysis [49,128,130,131,137]. This approach reduces the number of associated factors by showing clusters according to the separation between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation